2020
DOI: 10.26740/ujced.v9n3.p344-353
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Software Anti Chemmisco Dengan Strategi Conceptual Change Text Pada Materi Laju Reaksi

Abstract: Penelitian pengembangan ini memiliki tujuan untuk mengembangkan software anti chemmisco sebagaimedia pendeteksi dan pereduksi miskonsepsi peserta didik dengan strategi conceptual change text padamateri laju reaksi. Pengembangan software ini ditinjau berdasarkan kelayakan software dari tiga kriteria.Kelayakan software yang dikembangkan ditinjau dari validitas, kepraktisan dan keefektifan. Metode yangdigunakan dalam pengembangan software ini yaitu metode Research and Development (R&D). Uji cobaterbatas dilak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…This research is highly feasible because student interest and success in activities occur in the learning process (Mandasari & Sukarmin, 2020;Yumuşak et al, 2015). This is evident from the reading material using simple, concise, and straightforward language.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research is highly feasible because student interest and success in activities occur in the learning process (Mandasari & Sukarmin, 2020;Yumuşak et al, 2015). This is evident from the reading material using simple, concise, and straightforward language.…”
Section: Discussionmentioning
confidence: 99%
“…Misconceptions are conceptual errors that are caused when learning occurs when there is a discrepancy with the scientific concept. Students who experience misconceptions must be immediately reduced so that they do not have a negative impact on learning outcomes and do not affect further understanding of concepts (Mandasari & Sukarmin, 2020). Natural science concepts have a connected character, if there is a wrong understanding of the concept, it will affect other concepts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Gündoğdudkk., (2011) that the use of computer simulation is effectively applied in learning, it makes it easier for teachers to present material and develop students' understanding of the concepts of the material being studied. Furthermore, Sumargo & Yuanita (2014) revealed that the use of PhET simulation is a new thing for students which can increase learning motivation. Prihatiningtyas et al, (2013) also confirmed that the application of PhET simulation in learning can improve students' psychomotor learning outcomes.…”
Section: Figures 1 Acid Base Phet Simulation Displaymentioning
confidence: 99%
“…Conceptual change text is a learning strategy based on constructivism and thinking skills (Parniyanda & Sukarmin, 2022). In addition to the right strategy, learning media are also very important to use in the learning process (Mandasari &;.…”
Section: ▪ Introductionmentioning
confidence: 99%